2022
DOI: 10.18203/2319-2003.ijbcp20223355
|View full text |Cite
|
Sign up to set email alerts
|

A study of reporting pattern of adverse drug reactions in a tertiary care teaching hospital

Abstract: Background: Adverse drug reactions (ADRs) are one of the prime causes of morbidity and mortality, increase in hospital stay and socioeconomic burden on the patients. Periodic monitoring aids in formulating methods for safe usage of medicines in hospitals. Identification of ADRs and their reporting pattern can provide useful information for their prevention. Hence this study was done to see the pattern of reported ADRs in Patna Medical College and Hospital, Patna in a 3 months of study.Methods: It was an observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The NPPV of India was launched in 2010 to monitor the safety of drugs in India, but the reporting of ADRs is still voluntary, and under-reporting is a major problem. 17 A study published in the Indian Journal of Medical Sciences in 2021 found that the reporting rate of ADRs to antimicrobials in India was only 0.07%, which is much lower than the estimated incidence of ADRs. 18 The current study was to identify the incidence and pattern of adverse drug effects (ADRs) of antimicrobial drugs.…”
Section: Adverse Drug Reaction Monitoring Of Commonly Prescribed Anti...mentioning
confidence: 97%
See 1 more Smart Citation
“…The NPPV of India was launched in 2010 to monitor the safety of drugs in India, but the reporting of ADRs is still voluntary, and under-reporting is a major problem. 17 A study published in the Indian Journal of Medical Sciences in 2021 found that the reporting rate of ADRs to antimicrobials in India was only 0.07%, which is much lower than the estimated incidence of ADRs. 18 The current study was to identify the incidence and pattern of adverse drug effects (ADRs) of antimicrobial drugs.…”
Section: Adverse Drug Reaction Monitoring Of Commonly Prescribed Anti...mentioning
confidence: 97%
“…A study published in the Indian Journal of Pharmacology in 2022 found that the incidence of ADRs to antimicrobials in India was 17.7%, with the most common ADRs being skin reactions, gastrointestinal reactions, and allergic reactions. 17 In terms of ADR reporting on antimicrobials, India is still in its early stages. The NPPV of India was launched in 2010 to monitor the safety of drugs in India, but the reporting of ADRs is still voluntary, and under-reporting is a major problem.…”
Section: Adverse Drug Reaction Monitoring Of Commonly Prescribed Anti...mentioning
confidence: 99%